Age depth model of Black Sea sediment cores covering MIS 6 (184-130 ka BP) - Wegwerth, Antje (In supplement to: Wegwerth, Antje; Dellwig, Olaf; Wulf, Sabine; Plessen, Birgit; Kleinhanns, Ilka C; Nowaczyk, Norbert R; Jiabo, Liu; Arz, Helge Wolfgang (2019): Major hydrological shifts in the Black Sea “Lake” in response to ice sheet collapses during MIS 6 (130–184 ka BP). Quaternary Science Reviews, 219, 126-144, https://doi.org/10.1016/j.quascirev.2019.07.008, 2019)
Age-depth relation of composite core from MSM33 expedition constructed by correlation of the d18Oostracod record of the composite core with d18O records of speleothems from Sofular Cave (Anatolia; Badertscher et al., 2011) and Abaliget Cave (Hungary; Koltai et al., 2017). Further age control points come from the tephra analyses (doi:10.1594/PANGAEA.906238).
Keywords: Black Sea "Lake"; Eurasia; Meltwater; MIS 6; palaeohydrology; Pleistocene; Saalian glaciation